Pelatihan Digital Marketing Berbasis Instagram Di CV Kurnia Barokah Jepara - Nur Aeni Widiastuti; Achmad Zainudin; Dhabitha Laviana Filza; Ahmad Putra Prayoga; Ahmad Muzakki (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2022)
Success in a business, both small and large, is supported in terms of the selection of marketing media. Therefore, determining the selection of marketing media as a supporter of business success needs to be considered by looking at environmental conditions and the times. Seeing the times, the business world is currently competing in the digital industry, one of which is digital marketing. Digital marketing is an effort that aims to promote a product or service using media that depends on digital transmission. Such as media promotion in CV.Kurnia Barokah. The gift of Barokah is still conventional, that is, only by word of mouth so that the results of marketing have not yet received optimal results. Innovation in the use of effective promotional media can provide optimal results as expected, such as the use of Instagram-based digital marketing. To overcome this problem by holding digital marketing training at CV. Karunia Barokah. The output of this activity is an increase in partner knowledge about Instagram-based digital marketing.